THE BAKERY INDUSTRY OF UKRAINE: TRANSFORMATIONS AND CHALLENGES IN WARTIME - MOROZ, SVITLANA; KALASHNYK, OLENA; KAROLOP, OLENA; BARABOLIA, OLHA; KITAYGORA, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article examines the transformations within Ukraine’s bakery industry, focusing on the consolidation of large-scale production and the increasing presence of private manufacturers targeting local markets. The sector has undergone significant structural changes due to economic instability and the ongoing war, which has disrupted supply chains, increased production costs, and altered consumer demand. One of the major challenges faced by the industry is the rising cost of raw materials, energy, and transportation, driven by logistical disruptions and infrastructure damage caused by military aggression. The destruction of grain storage facilities, supply routes, and key production sites has severely impacted the availability and affordability of essential ingredients, leading to higher costs for both producers and consumers. Additionally, the war has forced many bakeries to adapt their business models, incorporating new logistical strategies and sourcing alternatives to maintain production despite adverse conditions. The article also explores the dynamics of Ukraine’s external trade in bakery products, analyzing how wartime restrictions and geopolitical shifts have reshaped export and import trends. While some international markets have remained accessible, others have been lost due to logistical constraints and economic sanctions. Despite these challenges, Ukraine continues to play a crucial role in global food security, supplying essential agricultural products to various countries worldwide. Furthermore, the study highlights ongoing efforts within the bakery industry to adopt innovative solutions, such as frozen dough technology, alternative grain sources, and efficiency-driven production methods. These adaptations help businesses remain competitive while ensuring a stable supply of bakery products in domestic and international markets.Ultimately, the resilience of Ukraine’s bakery sector amid wartime challenges underscores its critical role in the country’s food system and economic recovery.